So, what is translation to you? Lin Moniz, Maria & Lopes, Alexandra (eds.) (2017): The Age of Translation. Early 20th-century Concepts and Debates. Frankfurt am Main: Peter Lang - Sinner, Carsten (chronotopos – A Journal of Translation History, 2020)
A book review of the following publication: Lin Moniz, Maria & Lopes, Alexandra (eds.) (2017): The Age of Translation. Early 20th-century Concepts and Debates. Frankfurt am Main: Peter Lang (Passagem. Estudos em Ciências Culturais. Studies in Cultural Sciences. Kulturwissenschaftliche Studien 11). 253 p. Contributors and Subject Index. ISBN 978-3-631-71657-1